Answer:
Y - 12 < -32
Step-by-step explanation:
Choose 1 answer:
(Choice A)
1≤t≤4
(Choice B)
−4≤t≤−3
(Choice C)
−2≤t≤0
(Choice D)
−2≤t≤4
Answer:
In the interval of - 2 ≤ t ≤ 4, the average rate of change is zero.
Step-by-step explanation:
The function is given to be ............ (1)
(i) Now, for 1 ≤ t ≤ 4, we will put t = 1 and t = 4.
So, g(1) = 5, g(4) = - 4. {From equation (1)}
Hence, g(1) ≠ g(4)
(ii) Now, for - 4 ≤ t ≤ - 3, we will put t = - 4 and t = - 3.
So, g(- 4) = - 20, g(- 3) = - 11. {From equation (1)}
Hence, g(- 4) ≠ g(- 3)
(iii) Now, for -2 ≤ t ≤ 0, we will put t = - 2 and t = 0.
So, g(- 2) = - 4, g(0) = 4. {From equation (1)}
Hence, g(- 2) ≠ g(0)
(iv) Now, for - 2 ≤ t ≤ 4, we will put t = - 2 and t = 4.
So, g(- 2) = - 4, g(4) = - 4. {From equation (1)}
Hence, g(- 2) = g(4)
Therefore, in the interval of - 2 ≤ t ≤ 4, the average rate of change is zero. (Answer)
For this case we have the following quadratic equation:
Where:
We find the solution by:
Substituting the values we have:
Thus, we have two roots:
Answer:
Answer: -8
Step-by-step explanation:
We must remember that, in geometric sequences, the ratio between the consecutive terms is constant.This is called "Common ratio" and is represented with "r".
We need to find the common ratio of this geometric sequence:
Divide one term by the previous term:
Then, the next term asked in the exercise can be found by multiplying -4 by 2.
Therefore, this is:
Answer:
-8
Step-by-step explanation:
r=2
so multiply third term by 2
this is your equation; x - 3 =11
and this is how you solve it;
x-3 =11
x -3 + 3 = 11+3
x = 14
and if you want to check it;
x - 3 =11
14 -3 =11
11 =11
Hope that helps:)
No need to solve just need equation